2017
DOI: 10.3892/etm.2017.4428
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and correlation of HIF-2α, VEGFA and EphA2 in residual hepatocellular carcinoma following high-intensity focused ultrasound treatment: Implications for tumor recurrence and progression

Abstract: Abstract. Rapid growth of residual tumors can occur as a result of their recurrence and progression. The present study aimed to investigate the expression of hypoxia inducible factor-2 subunit α (HIF-2α), vascular endothelial growth factor A (VEGFA), erythropoietin-producing hepatocellular A2 (EphA2) and angiogenesis in residual hepatocellular carcinoma (HCC), following treatment with high-intensity focused ultrasound (HIFU) ablation, in order to investigate the association between protein expression and tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…VEGF, a key factor in angiogenesis, and EphA2 are associated with endothelial cell migration, paracellular permeability and tumor neovascularization (30,31). Reportedly, EphA2 is involved in VEGF-induced vascular assembly and tumor angiogenesis, which are indicators of tumor recurrence and progression (32,33). Previously, it was revealed that EphA2 activation in gastric cancer cells was triggered by VEGF release upon treatment with CAF-CM (14).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, a key factor in angiogenesis, and EphA2 are associated with endothelial cell migration, paracellular permeability and tumor neovascularization (30,31). Reportedly, EphA2 is involved in VEGF-induced vascular assembly and tumor angiogenesis, which are indicators of tumor recurrence and progression (32,33). Previously, it was revealed that EphA2 activation in gastric cancer cells was triggered by VEGF release upon treatment with CAF-CM (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors suggested HIFU ablation might result in the hypoxia condition of residual tumor and induce tumor angiogenesis via HIF-1, 2α/VEGFA/EphA2 (Wu et al, 2014). Two other studies conducted by Wu et al (2017); Wu et al (2021) also demonstrated that overexpression of EphA2, VEGFA, and HIF-2α were closely associated with angiogenesis in residual HCC after HIFU ablation. Moreover, the expression of EphA2, VEGFA, and HIF-2α could be significantly inhibited by sorafenib (Wu et al, 2021).…”
Section: Clinical Implications Of Hif-1α In Hcc After Ablationmentioning
confidence: 96%
“…However, at lower intensities (0.1–1.0 W/cm 2 ), FUS is not cytotoxic and has, in fact, been shown to stimulate cell proliferation, as demonstrated in studies with bone marrow stem cells and peripheral neuronal cells [ 18 , 19 ]. In addition, recent evidence shows that standalone HIFU may promote tumor recurrence and progression in aggressive liver cancer [ 20 ] and cannot prevent rapid tumor recurrence in ~50% of patients with intermediate-risk (T2b) or high-risk (T2c-T4), localized PCa [ 21 , 22 ]. Therefore, it is envisioned that the utility of moderate FUS doses (0.1–0.9 kW/cm 2 ) may have profound clinical application towards a targeted elimination of localized PCa, and novel strategies to enhance the anticancer efficacy of FUS are clearly warranted.…”
Section: Introductionmentioning
confidence: 99%